Perceived Stress and Psychological Impact Among Healthcare Workers at a Tertiaty Hospital in China During the COVID-19 Outbreak: The Moderating Role of Resilience and Social Support - Zhang, Qiaoyang; Dong, Guanzhong; Meng, Weifen; Chen, Zhuoyou; Cao, Yin; Zhang, Min (Frontiers in Psychiatry, 2022)
Aims To investigate the psychological distress experienced by healthcare workers (HCWs) at a tertiary hospital in Changzhou, China, outside Wuhan, during the early stage of COVID-19 and evaluate the moderating effects of resilience and social support on the relationship between stress and psychological distress. Methods The study was conducted between February 10 and 15, 2020, in a non-probabilistic way. The survey included questions regarding the risk of exposure, sociodemographics, perceived stress [10-item Perceived Stress Scale (PSS-10)], resilience [10-item Connor–Davidson Psychological Resilience (CD-RISC-10)], social support [Multidimensional Scale of Perceived Social Support (MSPSS)], and psychological distress [12-item General Health Questionnaire (GHQ-12)]. We applied the PROCESS macro for SPSS to test the hypotheses that resilience and social support moderated the stress response. In addition, a simple slope analysis was conducted when the interaction effect was statistically significant. Results Some 33.6% of participants suffered from psychological distress (GHQ-12 ≥ 12). Perceived stress was positively related to psychological distress (r = 0.42, p < 0.001). In addition, resilience (ΔR2 = 0.03, p for interaction < 0.001) and social support (ΔR2 = 0.01, p for interaction <0.01) moderated the stress response. The impact of perceived stress on psychological distress was attenuated when subjects who were resilient (high β = 0.15, p < 0.001; low β = 0.36, p < 0.001), and perceived stress had less impact on psychological distress when social support was high (β = 0.24, p < 0.001) rather than low (β = 0.34, p < 0.001). Limitations The cross-sectional design led to a lack of causal relationships between variables. Conclusions Our data showed that resilience and social support moderated the stress response among HCWs in the pandemic, suggesting that improving resilience and social support could be appropriate targets to improve HCWs' mental health in the pandemic.